Manajemen Pendidikan Sekolah dan Kualitas Pendidikan (Studi pada Kualitas Pendidikan di Provinsi Papua) - Indubri, Paulus Yulius; Idrus, M. S.; Salim, Ubud; Djumahir (Jurnal Aplikasi Manajemen, 2013)
This research is to analyze the effect about empirically test: 1) whether professional teacherinfluences to school education managements, 2) whether ascendant curriculum to schooled education managements, 3) if yielding learned influential to schooled education managements, 4) if professional teacher influentialing to education qualities, 5) if ascendant curriculum to education qualities, 6) if yielding learned influential to education qualities, and 7) what is influential schooled education managementto education quality. Observational method that is utilized is format design affiliate approaching (mixing approach), which is supported quantitative approaching by qualitatif's approaching as minor approaching. Observational location on 20 Regencies/City that exist on Papua Province region with division as follows: 1) Regencies/Cities at Province upstate Papuan, namely: Jayapura city, Jayapura regency, Keeromregency, Sarmi regency, Supiori regency, Fertile regency, Nabire regency, Yapen regency, and Waropen Regency,2) Regencies/Cities at Papua Province middle part, namely: Jayawijaya regency, Paniai regency, Mimika regency, Tolikara regency, Pegunungan Bintang regency, Puncak Jaya regency, and Yahukimo regency, and 3) Regency/City at austral Papua Province, namely: Merauke regency, Asmat regency, BovenDigoel regency, and Mappi Regency. The Result show that: 1) marks sense kausal's relationships among teachers professional factor, curriculum, learned result, education management to education quality, 2) schooled education managements constitute education quality determinants, but then also so prescribed by professional teacher, curriculum, and tall studying result. If education management corresponds to thatexpected deep its management therefore good education quality will be reached conversely.